2019
DOI: 10.1002/chem.201901695
|View full text |Cite
|
Sign up to set email alerts
|

Chirality‐Controlled Self‐Assembly of Amphiphilic Dibenzo[6]helicenes into Langmuir–Blodgett Thin Films

Abstract: Racemic and highly enantioenriched 3‐methoxycarbonyl, 3‐carboxy, and 3‐hydroxymethyl derivatives of dibenzo[6]helicene were prepared. The Langmuir layers of these helicenes were formed at the air–water interface and transferred onto solid substrates to afford Langmuir–Blodgett films, which were then studied by ambient atomic force microscopy and (chir)optical spectroscopy. Significant differences were found in the behaviour of the Langmuir layers as well as in the morphology, UV/Vis, electronic circular dichro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…320 Very recently, Starýand co-workers studied the ECD properties of highly enantioenriched 3-methoxycarbonyl, 3-carboxy, and 3-hydroxymethyl derivatives of dibenzo [6]helicene as Langmuir−Blodgett films, discussing the impact of molecular chirality and chemical nature of the polar group (i.e., ester vs carboxyl vs hydroxyl) on the self-assembly at the air−water interface. 321 Although 1,1′-binaphthyl derivatives (and other similar biaryl compounds with axial chirality) have represented a milestone in the field of solution ECD measurements (especially for conformational analysis), 56 for a long time the chiroptical investigation of their thin films was only little considered; some papers describing second-harmonic generation circular dichroism (SHG-CD) experiments of enantiopure 1,1′-bi-2-naphthol (BINOL) monolayers at the air/quartz surface were published in 1994 by Hicks and co-workers, 279,322,323 while in 2005 a similar SHG-CD study was performed by Conboy et al on Langmuir−Blodgett−Schaefer thin films of (S)-and (R)-BINOL. 324 However, in the last 10 years, the ECD study of 1,1′-binaphthyl derivatives in thin films gained considerable interest.…”
Section: Ecd In Thin Films Of π-Conjugated Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…320 Very recently, Starýand co-workers studied the ECD properties of highly enantioenriched 3-methoxycarbonyl, 3-carboxy, and 3-hydroxymethyl derivatives of dibenzo [6]helicene as Langmuir−Blodgett films, discussing the impact of molecular chirality and chemical nature of the polar group (i.e., ester vs carboxyl vs hydroxyl) on the self-assembly at the air−water interface. 321 Although 1,1′-binaphthyl derivatives (and other similar biaryl compounds with axial chirality) have represented a milestone in the field of solution ECD measurements (especially for conformational analysis), 56 for a long time the chiroptical investigation of their thin films was only little considered; some papers describing second-harmonic generation circular dichroism (SHG-CD) experiments of enantiopure 1,1′-bi-2-naphthol (BINOL) monolayers at the air/quartz surface were published in 1994 by Hicks and co-workers, 279,322,323 while in 2005 a similar SHG-CD study was performed by Conboy et al on Langmuir−Blodgett−Schaefer thin films of (S)-and (R)-BINOL. 324 However, in the last 10 years, the ECD study of 1,1′-binaphthyl derivatives in thin films gained considerable interest.…”
Section: Ecd In Thin Films Of π-Conjugated Small Moleculesmentioning
confidence: 99%
“…In 2018, Iimura et al reported a detailed investigation on the helically distorted [1,1′-bibenzo­[ c ]­phenanthrene]-2,2′-diol (HEBPOL): thanks to the amphiphilic character arising from the presence of both hydrophobic aromatic rings and hydrophilic −OH groups, it is able to form stable layers at the air–water interface, which were transferred to solid substrates by Langmuir–Blodgett technique; the ECD properties of the obtained films were then investigated and compared with those of spin-coated samples . Very recently, Starý and co-workers studied the ECD properties of highly enantioenriched 3-methoxycarbonyl, 3-carboxy, and 3-hydroxymethyl derivatives of dibenzo[6]­helicene as Langmuir–Blodgett films, discussing the impact of molecular chirality and chemical nature of the polar group (i.e., ester vs carboxyl vs hydroxyl) on the self-assembly at the air–water interface …”
Section: Ecd Properties In Thin Films Of π-Conjugated Systems: Litera...mentioning
confidence: 99%
“…Holec et al researched the behavior of chiral amphiphilic dibenzo [6]helicenes at the air−water interface and their transferred LB films (Figure 19). 147 Although these compounds do not possess long alkyl chains, their 2D assemblies at the air− water interface are somehow formed. Detailed analyses by surface pressure isotherms, UV−vis spectroscopy, electronic circular dichroism, fluorescence spectroscopy, and atomic force microscopy with the aid of a molecular dynamics computational approach revealed the important roles of compound chirality and attached polar functional groups in their 2D assembled structures.…”
Section: ■ For Applicationsmentioning
confidence: 99%
“…Feng et al [11] have utilized hydrophobic interactions to deposit amide-containing helicenes on alkylated quartz via the Langmuir-Blodgett technique. Some other helicenes that are used for the production of Langmuir-Blodgett thin films include 2-amino[6]helicene derivatives [12], thiohelicene bisquinone [13], and dibenzo[6]helicene derivatives [14].…”
Section: Introductionmentioning
confidence: 99%